Analysis of the Influence of Perceived University Support on Entrepreneurial Intention of Entrepreneurial Students Through Attitude, Norm, and Self-Efficacy - Yohana, Corry; Safariningsih, Ratna Tri Hari; Tresna, Alaida Bagus; Fidhyallah, Nadya Fadillah; Puruwita, Dita (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2025)
This study examines the effect of perceived university support on entrepreneurial intention through attitude toward entrepreneurship, subjective norms, and entrepreneurial self-efficacy among university students enrolled in entrepreneurship programs or engaged in entrepreneurship activities. Using a quantitative causal design, data were collected via an online questionnaire from 210 students involved in entrepreneurial activities in higher education. The research employed five main variables measured on a 6-point Likert scale and analyzed using Structural Equation Modeling (SEM) with SmartPLS 4. Findings reveal that perceived university support positively and significantly influences attitude toward entrepreneurship, subjective norms, and entrepreneurial self-efficacy, which in turn, substantially affect entrepreneurial intention. university support indirectly shapes students’ entrepreneurial intentions through mediating factors. This study enriches entrepreneurship literature in higher education and provides practical implications for universities and policymakers to enhance institutional support for fostering students’ entrepreneurial aspirations.